Vascular and platelet hemostasis and microcirculation in arterial hypertension patients - L. L. Kirichenko; A. P. Sharandak; O. S. Tseka; A. P. Korolev; O. V. Vostryakova; Zh. I. Vasheva; Yu. A. Babich (Кардиоваскулярная терапия и профилактика, 2005)
The article is focused on the role of endothelium and vasoactive endothelial factors in arterial hypertension (AH) development. Special attention is given to platelet functional state, blood rheology, and microcirculatory disorders’ role in AH pathogenesis.